1993
DOI: 10.1177/030006059302100302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prostaglandin E1 on the Renin – Aldosterone System in Patients with Diabetic Nephropathy

Abstract: The effect of prostaglandin E1 (PGE1) on the renin-aldosterone system was investigated in hospitalized patients with non-insulin-dependent diabetes mellitus presenting with continuous proteinuria but without nephrotic syndrome. Of the 20 patients studied, 10 had continuous positive proteinuria > or = 200 mg/day and 10 had continuous positive proteinuria < 200 mg/day. Prostaglandin E1 (40 micrograms in 100 ml normal saline) was infused intravenously over 2 h twice daily for 4 weeks. Plasma renin activity (PRA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Alprostadil (Prostaglandin E1, PGE1) is one of hormones synthesized by most tissues 8 to regulate blood flow in variety of organs 9 , 10 . In the clinical, PGE1 may have positive effects on DN by improving renal blood circulation, decreasing albuminuria and lessening proteinuria 11 , 12 . It has been not reported that PGE1 has the potential protection on insulin resistance in renal tubule epithelial cells via autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Alprostadil (Prostaglandin E1, PGE1) is one of hormones synthesized by most tissues 8 to regulate blood flow in variety of organs 9 , 10 . In the clinical, PGE1 may have positive effects on DN by improving renal blood circulation, decreasing albuminuria and lessening proteinuria 11 , 12 . It has been not reported that PGE1 has the potential protection on insulin resistance in renal tubule epithelial cells via autophagy.…”
Section: Introductionmentioning
confidence: 99%